Evaluation of quantitative changes, pollution indexes and distribution of heavy metals Pb and Cd in the dust falling (case study: Zahedan city) - Sara Abdollahi; HamidReza Azimzadeh; MohammadReza Ekhtesasi; Asghar Mosleh-Arani (علوم محیطی)
Introduction: Dust is one of the phenomena of atmospheric and natural disasters that poses adverse environmental effects and impacts. Due to the wide distribution of dust, this phenomenon can also change the soil and its biology trends. Typically, dust particles have a diameter of less than 100 microns, which can be transmitted horizontally or vertically to the ground after miles. The aim of this study was to determine the amount of dust falling and heavy metals lead and cadmium concentrations in dust samples to evaluate these elements is the urban pollution.Material and methods: In this study, samples were collected using mild sediment trap for six months.A total of 180 samples were collected. Samples were weighed accurately using a scale of 0.001 g. The analysis of samples was performed using ISO11466. The samples were extracted by the Institute of Water and Soil Research, and the concentration of heavy metals was measured by the atomic absorption spectrometry of the Analyti jena-951 model.Results and discussion: The results showed that in the winter of March and in the spring of June, the highest rate of dust was observed. The mean lead concentration in winter was 97.32 ± 5.40 mg.kg and 90.16 ± 5.93 mg.kg in spring. Also, the average cadmium concentration in winter was 37.19 ± 3.60 mg.kg and 29.62 ± 2.42 mg.kg in the spring. According to the pollution index (PI), the level of contamination of lead is high in the floor, however, according to this index, cadmium contamination in both seasons is more than the level of contamination of lead and is higher than the limit, which is the risk index The ecology of cadmium, with an average of 1673.98 and 1333.03, also confirms this and is in the hazardous area of contamination. Also, the ecological risk of lead metal in winter was 18.14 ± 1.01 and in the spring with a mean of 16.91 ± 1.11 in the low pollution class. According to the values obtained for the pollution load index (PLI), this contamination rate is Cdwinte r˃Cdspring˃Pbwinter˃Pbsprin, and both of these elements are highly polluted in the classroom.Conclusion: The results of statistical calculations and contamination levels indicate that the amount of dust pollution to lead and cadmium is higher than most of the calculated indices in the classes with high to high contamination.Therefore, these elements have been brought into the environment as a result of human activities and have less natural origin.